RELATIONSHIPS BETWEEN ORTHOREXIA NERVOSA TENDENCY, MINDFUL EATING, AND BODY MASS INDEX IN YOUNG ADULTS (19-32 AGED): A CROSS-SECTIONAL STUDY BASED ON GENDER DIFFERENCES - Murat Altan; Şemsi Gül Yılmaz Kocaman; Hasan Yıldırım (Karya Journal of Health Science, 2026)
Objective: This cross-sectional study investigated the associations between Orthorexia Nervosa (ON), mindful eating, and body mass index (BMI) among young adults, and explored gender-based differences in ON tendencies and mindful eating.Method: The research was conducted between October and December 2024 in Elazığ, Türkiye, and included 757 healthy participants. Data were collected using face-to-face questionnaires assessing sociodemographic characteristics, the Orthorexia Nervosa-11 Scale (ORTO-11), and the Mindful Eating Questionnaire (MEQ). Anthropometric measurements were obtained to calculate BMI, and a p-value of